دراسة تغيرات الخواص الضوئية لزيت الزيتون، وزيت عباد الشمس (Latakia University Journal -Basic Sciences Series, 2018)
يهدف هذا العمل إلى دراسة بعض الخواص الضوئية مثل: الامتصاصية، النفوذية، ومعامل الاضمحلال لزيت الزيتون وزيت عباد الشمس وذلك من أجل ضوء وحيد اللون طول موجته من 366 – 578 نانو متر. إضافة إلى ذلك، تم مزج زيت الزيتون مع زيت عباد الشمس بنسب مئوية مختلفة، ثم درس المزيج الناتج ضوئياً. تستخدم الدراسة الطيفية للكشف عن نقاوة الزيت وتأثير الضوء عليه من خلال عمليات الامتصاص، والتشتت والاستقطاب. إن أهم النتائج التي تم التوصل إليها هي: لا يعطي تطبيق الضوء الأصفر معلومات هامة حول خواص الزيت – يمتص زيت الزيتون الضوء البنفسجي وفوق البنفسجي، وبالتالي يمكننا الحصول على معلومات عن مكونات الزيت – الكشف عن عملية الغش التي تتم بوسائل مختلفة. This work aims at studying some optical properties of olive oil and sunflower oil such as absorption, transmission and extinction coefficient for monochromatic light. The wave lengths, that are applied, are between 366-578 nm. In addition, different percentages of olive oil and sun flower oil were mixed. The mixture was them optically studied. The spectral investigation of oil is used to probe its purity and its light influence on it through absorption, scattering and polarization processes. This study concludes that the application of the yellow light doesn’t give us relevant information about the properties of oil, olive oil absorbs violet and ultraviolet light, therefore can give information about oil constituents, and that deceit which is done by different means can be detected.